Program Pembinaan Mutu Guru Oleh Unit Pelaksana Teknis Daerah (UPTD) Pendidikan Kecamatan Kota Ternate Utara 202 - Mohtar Kamisi; Rustam Hasyim (Universitas Khairun, 2023)
This research discusses the Teacher Quality Development Program by the Regional Technical Implementation Unit (UPTD) of North Ternate City District Education 2022. The purpose of this study is to analyze the development of educational unit supervisors including professional development and career development. Professional development is directed at improving and developing professional abilities so that they can carry out supervisory functions, both academic supervision and managerial supervision. The method used in this study is a qualitative method that is descriptive of how the implementation of the teacher quality development program by the regional technical implementation unit (UPTD) of North Ternate City Education District 2022. The research site was carried out at the Regional Technical Implementation Unit (UPTD) of North Ternate City District Education 2022 from October to November 2022. Data collection techniques used observation, questionnaires, and documentation. The data analysis techniques include; data reduction, data presentation and conclusion. The results of this study found several things; (1). The supervisor of the education unit is appointed with the task of conducting guidance and supervision of education in the educational unit or school that is under his supervision. Supervision of educational units includes academic supervision and managerial supervision. (2). Academic supervision aims to assist or foster teachers in improving the quality of the learning process in order to obtain more optimal student learning outcomes. Meanwhile, managerial oversight aims to assist and foster school principals in their efforts to improve the quality of education through optimizing school performance. In carrying out their duties and responsibilities as supervisors of educational units/schools, basic skills are required as professional supervisors